A new constitutional framework for Sri Lanka : proposals from business and civil society - Gomez, Mario; Gomez, Mario; Berghof Foundation for Conflict Studies. Sri Lanka Office; Ad Hoc Group on 'Power Sharing for a Peaceful Constitutional Settlement.' (Colombo : Berghof Foundation for Conflict Studies--Sri Lanka Office, 2007)
Contributed recommendations of the Ad Hoc Group on 'Power Sharing for a Peaceful Constitutional Settlement' initiated on 23rd August 2006 in response to a public notice issued by government of Sri Lanka.
Keywords: Constitutional law -- Sri Lanka